FIGURE 23. Shackletonia robusta K.H in Revision of the lysianassoid genera Acidostoma and Shackletonia (Crustacea: Amphipoda: Acidostomatidae fam. nov.) - Stoddart, H.E.; Lowry, J.K. (Zenodo, 2012)
FIGURE 23. Shackletonia robusta K.H. Barnard, male, 22.4 mm, MV J38209, Prydz Bay, Antarctica. : Published as part of Stoddart, H.E. & Lowry, J.K., 2012, Revision of the lysianassoid genera Acidostoma and Shackletonia (Crustacea: Amphipoda: Acidostomatidae fam. nov.), pp. 1-34 in Zootaxa 3307 (1) on page 27, DOI: 10.11646/zootaxa.3307.1.1, http://zenodo.org/record/5250488